Cellulose Acetate Derived Free-Standing Electrospun Carbon Nanofibrous Mat as Anode Material for Rechargeable Lithium-Ion Battery. (25th October 2017) - Kakunuri, Manohar; Araga, Ramya; Khandelwal, Mudrika; Sharma, Chandra Shekhar
Abstract : In this work, we first electrospun cellulose acetate into nanofibers followed by deacetylation using NaOH in ethanol solution. Deacetylation of cellulose acetate fiber mat regenerated cellulose to yield cellulose nanofibers as confirmed by Raman spectroscopy. Further, as-obtained cellulose nanofibers were pyrolyzed at 900 °C in the inert atmosphere to yield cellulose acetate derived electrospun carbon nanofibers. Morphological changes during deacetylation and carbonization were examined by SEM imaging. Almost 55% shrinkage was observed during pyrolysis to finally obtain carbon nanofibers with average diameter 474.1 nm. This cellulose acetate derived free standing carbon nanofiber mat was then assembled as an anode in half-cell configuration without using any binder and then tested for its electrochemical performance using cyclic voltammetry and charge/discharge experiments. At 37.2 mA/g current density (0.1 C rate), specific capacity value after 100 cycles was stabilized at 290 mAh/g.